Development of Problem-Based Learning E-Module Integrated with Scientific Literacy on Acid-Base Concepts for Grade XI Students - Pasion Tarigan; Herlinawati Herlinawati (Universitas Tadulako, 2025)
In learning chemistry, especially acid-base materials, students still have difficulty understanding abstract concepts and show low science literacy. Therefore, it is necessary to develop teaching materials in the form of e-modules based on Problem-Based Learning (PBL) integrated with science literacy to improve students' understanding of concepts and critical thinking skills. This study aims to: (1) Determine the level of validity of the e-module of chemistry learning based on PBL integrated with science literacy on acid-base material for grade XI SMA, (2) Determine student responses to the e-module of chemistry learning based on PBL integrated with science literacy on acid-base material for grade XI SMA. This type of research is research and development (R&D) with a 4D development model, but is limited to a 3D model. The stages carried out include the definition stage, to analyse things that need to be done, including front-end analysis, student analysis, task analysis, and concept analysis. The design stage is to design an e-module product on acid-based material. The development stage aims to validate the e-module that has been designed and revised based on the validator's suggestions, and then a practicality test is carried out based on student responses. The assessment instruments used in this study were validation questionnaires from material experts and media experts, as well as student response questionnaires. The assessment scale used was a Likert scale with a score range of 1-4. The results of the study showed that: (1) The average percentage of assessments given by material expert validators was 94.36% with a very valid category, while the average percentage of assessments given by media expert validators was 95.19% with a very valid category. (2) The results of the practicality test obtained from student responses obtained an average percentage value of 88.78%, with a very practical category.